Etiology research on different types of uveitis - Zhe Yang (Guoji Yanke Zazhi, 2016)
AIM:To analysis and discuss etiology of different types of uveitis. METHODS:We selected 60 patients(120 eyes)with uveitis treated in our hospital from June 2012 to June 2015. All patients examined by the same uveitis specialist with unified standards. According to international standards, uveitis was customized into:anterior uveitis(AU), intermediate uveitis(IU), posterior uveitis(PU), panuveitis(PanU). Age, gender, type of uveitis and causes of the disease were analyzed. RESULTS:Through the analysis of the etiology and clinical types of patients, the main types were idiopathic(26 cases, 21.7%), VKH syndrome(18 cases, 15.0%), HLA-B27 related(14 cases, 11.7%), viral(12 cases, 10.0%), Fuchs syndrome(8 cases, 6.7%), Behcet's disease(8 eyes, 6.7%), diabetes(6 eyes, 5.0%), syphilis(6 eyes, 5.0%), Posner-Schlossman syndrome(6 eyes, 5.0%), juvenile chronic arthritis(4 eyes, 3.3%), sympathetic ophthalmia(4 eyes,3.3%), traumatic(2 eyes, 1.7%), sarcoid(2 eyes, 1.7%), endophthalmitis(2 eyes, 1.7%)and others(2 eyes, 1.7%). By the observation for different types uveitis, the main cause of AU was idiopathic, followed by HLA-B27-related and viral; for PanU, it was VKH syndrome, idiopathic ones and Behcet's disease; for PU, it was idiopathic, then viral; for IU, it was idiopathic. CONCLUSION:Through observation and analysis for clinical patients, male patients were more than female; idiopathic, caused by VKH syndrome, viral and Behcet's disease are the common types of uveitis.